2015
DOI: 10.1159/000431185
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use Is Associated with Bladder Pain Syndrome/Interstitial Cystitis: A Population-Based Case-Control Study

Abstract: Introduction: Statin may induce epithelial dysfunction of the bladder urothelium. Epithelial dysfunction was proposed as one of the major potential etiologies for bladder pain syndrome/interstitial cystitis (BPS/IC). In this study, we examined the association between statin use and BPS/IC using a population-based study. Subjects and Methods: This case-control study used the Taiwan Longitudinal Health Insurance Database. In total, 815 female subjects with BPS/IC and 4075 randomly selected female controls were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…produced in the muscle cells, including those of the heart, the extensive use of statin treatment may explain the epidemics of heart failure that have been observed in many countries [75]. Furthermore, case-control and cross-sectional studies have shown that statin use is observed significantly more often among patients with cataracts [76], hearing loss [77], suicidal ideation [78], peripheral neuropathy [79], depression [80], Parkinson's disease [81], interstitial cystitis [82], herpes zoster [83], impotency [84], cognitive impairments [85][86][87][88], and diabetes [89,90]. In some of these studies, the side effects disappeared with discontinuation of the statins and worsened with rechallenge [74,84,85].…”
Section: Adverse Effects From Statin Treatmentmentioning
confidence: 99%
“…produced in the muscle cells, including those of the heart, the extensive use of statin treatment may explain the epidemics of heart failure that have been observed in many countries [75]. Furthermore, case-control and cross-sectional studies have shown that statin use is observed significantly more often among patients with cataracts [76], hearing loss [77], suicidal ideation [78], peripheral neuropathy [79], depression [80], Parkinson's disease [81], interstitial cystitis [82], herpes zoster [83], impotency [84], cognitive impairments [85][86][87][88], and diabetes [89,90]. In some of these studies, the side effects disappeared with discontinuation of the statins and worsened with rechallenge [74,84,85].…”
Section: Adverse Effects From Statin Treatmentmentioning
confidence: 99%
“…These perceived adverse effects include a high incidence of muscle pain [3137], fatigue [38, 39], especially with exertion and exercise [40], idiopathic inflammatory myositis [41, 42], autoimmune myopathy [4346], psychiatric and cognitive symptoms (depression, confusion, aggression, memory loss [4755]), severe irritability [56], sleep disturbances [52], musculoskeletal disorders and injuries [57, 58], sudden sensorineural hearing loss [59] and gastrointestinal distress [60]. The second category includes later developing morbidities that may not be perceived by the users as a side effect, but are linked to statin treatment: Type-2 diabetes [27, 6164], particularly in women [6567], cancer [6871], liver dysfunction and failure [72, 73], cataracts [74, 75], amyotrophic lateral sclerosis (ALS), ALS-like conditions and other central motor disorders, e.g., Parkinson’s disease and cerebellar ataxia [7680], lupus-like syndrome [81], susceptibility to herpes zoster [8284], interstitial cystitis [85], polymyalgia rheumatic [86], kidney injury [87, 88] and renal failure [89].…”
Section: Commentarymentioning
confidence: 99%
“…In this study, the diagnosis of FM (ICD-9-CM code 729.1), which was with validity and accuracy according to those used in previous literatures (10,(30)(31)(32), during the study period was the study end-point. In order to keep the FM diagnoses as accurate as possible, only those who have had the diagnoses of FM for at least 3 times during the study period were thought to be the victims of FM in this study.…”
Section: Outcome and Relevant Variablesmentioning
confidence: 99%